RETHINKING L2 MOTIVATION RESEARCH: THE 2 × 2 MODEL OF L2 SELF-GUIDES. Issue 2 (May 2019) - Papi, Mostafa; Bondarenko, Anna Vitalyevna; Mansouri, Soheil; Feng, Liying; Jiang, Chen
Abstract: The present study proposed and tested a revision of the self-guides outlined in the L2 motivational self system (Dörnyei, 2005, 2009 ). Covering the previous conceptualization and measurement issues, ideal L2 self and ought-to L2 self were bifurcated by own and other standpoints, and reoperationalized based on the fundamental tenets of self-discrepancy theory (Higgins, 1987 ) and regulatory focus theory (Higgins, 1997 ). Confirmatory factor analysis supported the fitness of the model and its superiority over three alternative models based on data collected from 257 international students learning English as a second language at a major North American university. Multiple regression results showed that ought L2 self/own was the strongest predictor of motivated behavior. Ideal L2 self/own, ought L2 self/other, and ideal L2 self/other were the next predictors in order of strength. Furthermore, ideal L2 self/own predicted an eager strategic inclination in L2 behavior, whereas ought L2 self/own predicted a vigilant strategic inclination, supporting the core principle of the regulatory focus theory that individuals with different regulatory orientations pursue their goals in qualitatively different manners.